Early PQQ supplementation has persistent long‐term protective effects on developmental programming of hepatic lipotoxicity and inflammation in obese mice. Issue 4 (22nd December 2016) - Jonscher, Karen R.; Stewart, Michael S.; Alfonso‐Garcia, Alba; DeFelice, Brian C.; Wang, Xiaoxin X.; Luo, Yuhuan; Levi, Moshe; Heerwagen, Margaret J. R.; Janssen, Rachel C.; de la Houssaye, Becky A.; Wiitala, Ellen; Florey, Garrett; et al.
Abstract : Nonalcoholic fatty liver disease (NAFLD) is widespread in adults and children. Early exposure to maternal obesity or Western‐style diet (WD) increases steatosis and oxidative stress in fetal liver and is associated with lifetime disease risk in the offspring. Pyrroloquinoline quinone (PQQ) is a natural antioxidant found in soil, enriched in human breast milk, and essential for development in mammals. We investigated whether a supplemental dose of PQQ, provided prenatally in a mouse model of diet‐induced obesity during pregnancy, could protect obese offspring from progression of NAFLD. PQQ treatment given pre‐ and postnatally in WD‐fed offspring had no effect on weight gain but increased metabolic flexibility while reducing body fat and liver lipids, compared with untreated obese offspring. Indices of NAFLD, including hepatic ceramide levels, oxidative stress, and expression of proinflammatory genes ( Nos2, Nlrp3, Il6, and Ptgs2 ), were decreased in WD PQQ‐fed mice, concomitant with increased expression of fatty acid oxidation genes and decreased Pparg expression. Notably, these changes persisted even after PQQ withdrawal at weaning. Our results suggest that supplementation with PQQ, particularly during pregnancy and lactation, protects offspring from WD‐induced developmental programming of hepatic lipotoxicity and may help slow the advancing epidemic of NAFLD in the next generation. —Jonscher, K. R., Stewart, M. S., Alfonso‐Garcia, A., DeFelice, B. C., Wang, X. X., Luo, Y., Levi, M., Heerwagen, M. J. R., Janssen, R. C., de la Houssaye, B. A., Wiitala, E., Florey, G., Jonscher, R. L., Potma, E. O., Fiehn, O. Friedman, J. E. Early PQQ supplementation has persistent long‐term protective effects on developmental programming of hepatic lipotoxicity and inflammation in obese mice. FASEB J . 31, 1434–1448 (2017) www.fasebj.org